Benex extraction kit - Zaker, Makan; Jikia, Maia (Caucasus Journal of Health Sciences and Public Health, 2019)
Due to the history of dentistry dentists came a cross so many ups and downs regard the methods of approach for dental treatment. With evolving of technology dentists are trying to solve these problems step by step. For extracting a teeth ,either its fractured or not ,or impacted or not impacted ,dentists are used many different methods such as closed and open (surgical) extraction , many armamentarium used for these procedures to have the best outcome and result .There are some complications ,that make extraction hard , in some cases even post-operation problems may occur .Benex system (extraction kit )new method of tooth extraction with less error and less future complications ,it is way easier than common methods of extraction and more efficient surgically , medically and physically due to its minimal invasive extraction technique